2000
DOI: 10.4315/0362-028x-63.3.309
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Source Outbreak of Campylobacteriosis Traced to Chicken

Abstract: Poultry is a source of human campylobacteriosis, but a large continuous source outbreak, heretofore, has not been attributed to both a single source of poultry and single serotype of Campylobacter. Here we report an outbreak of C. jejuni affecting 6 catering college trainees and 13 patrons of a restaurant in southern England. An epidemiological investigation successfully tracked the outbreak source to the farm of origin. Frequency of occurrence of campylobacters and outbreak serotype distribution were determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
37
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(37 citation statements)
references
References 28 publications
0
37
0
Order By: Relevance
“…Continuous common-source outbreaks are usually associated with contaminated water supplies [3,4]. Only one foodborne continuous common-source outbreak of campylobacteriosis, due to the distribution of contaminated chicken from a single poultry producer, has been reported in the literature [5].…”
Section: Introductionmentioning
confidence: 99%
“…Continuous common-source outbreaks are usually associated with contaminated water supplies [3,4]. Only one foodborne continuous common-source outbreak of campylobacteriosis, due to the distribution of contaminated chicken from a single poultry producer, has been reported in the literature [5].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, a great number of outbreaks have been related to water, which has been considered an important transmission route 12 . Campylobacteriosis outbreaks have been associated mainly to chicken meat and their subproducts 9,19 . The consumption of food contaminated by C. jejuni, especially inadequately processed or partially cooked poultry has been considered the main transmission route of enteritis in human beings 20 .…”
Section: Introductionmentioning
confidence: 99%
“…During the slaughtering process, the gastrointestinal contents can be released and contaminate the chicken meat products. Furthermore, several studies have shown that a large proportion of retail chicken products contain C. jejuni (22,26,28). Thus, a better understanding of processes that contribute to the growth and survival of C. jejuni in chickens could lead to efficient intervention strategies for reducing C. jejuni population sizes in this natural reservoir.…”
mentioning
confidence: 99%